The 30-minute celebrity makeover miracle : - Zim, Steve (John Wiley & Sons, Inc., 2008)
Wouldn't you love to have the body of a movie star without spending countless hours working out to get there? Top Hollywood trainer and Weekend Today fitness expert Steve Zim shows you how to sculpt a phenomenal physique faster and easier than you ever thought possible. In just thirty minutes a day, three times a week, Zim's revolutionary combined cardio and weight-training program will help you ramp up your metabolic rate, burn fat faster than conventional workouts, and produce the body of your dreams.